Rural Potential Based Community Development for Enhancing Eco-Tourism Kalisidi Village Through Developing Fruit Seedlings Center - Fajrin Pramana Putra; Aulia Isdamaryanti; Thoriq Apriza Nurdin; Muhammad Iqbal Fauzan (Indonesian Student Association Study Center in Türkiye, 2025)
Kalisidi Village is located in the West-Ungaran District, Semarang Regency. The village has abundant natural resources and strong potential for ecotourism development. However, agricultural challenges such as limited seed storage facilities, suboptimal irrigation, and insufficient seedling quality hinder the maximization of this potential. This study aims to analyze and implement community development programs based on local resources by establishing a fruit seedling center that supports both agricultural productivity and ecotourism. Data were collected through the Participatory Rural Appraisal (PRA). The program was planned based on the issues found by FGD with the Kelompok Wanita Tani in Kalisidi Village, which were divided into three main aspects: technology, information, and human resource management. To resolve these issues, Team 134 of KKN-T Diponegoro University proposed several programs including constructing a greenhouse, providing grafting technique training, implementing an automatic irrigation system based on Real-Time Clock (RTC), and developing a database that includes mapping high-quality fruit commodity distribution in Kalisidi village. The greenhouse design uses a lightweight iron frame with UV-resistant plastic covering, which has proven to be effective and economical for small-scale farmers. Moreover, it improved seedling protection and survival rates, while simultaneously grafting training enhanced farmers’ technical capacity and increased the availability of high-quality seedlings. Additionally, the irrigation system optimized water use efficiency and reduced labor requirements, whereas the fruit database provided spatial information that supported agricultural planning and promotion of local commodities. As a result, these programs contributed to strengthening food security, improving economic opportunities, and supporting agro-edutourism in Kalisidi Village. The study concludes that integrating local resource-based community empowerment with technological innovation can enhance rural ecotourism and ensure sustainable agricultural development.